Persistent giant U wave inversion with anoxic brain injury - Peters, Matthew N. (Baylor Health Care System, 2013)
Various electrocardiographic changes have been reported in the setting of acute neurological events, among them large, upright U waves. In contrast, the occurrence of inverted U waves is strongly suggestive of cardiovascular disease, most commonly hypertension, coronary artery disease, or valvular abnormalities. Presented herein is the case of a 29-year-old man with previous anoxic brain injury (but without apparent cardiovascular disease) whose electrocardiogram demonstrated persistent giant inverted U waves.